Heat Stress Effects are Stronger on Spikelets Than on Flag Leaves in Rice Due to Differences in Dissipation Capacity. (28th July 2015) - Zhang, C. X.; Fu, G. F.; Yang, X. Q.; Yang, Y. J.; Zhao, X.; Chen, T. T.; Zhang, X. F.; Jin, Q. Y.; Tao, L. X.
Abstract: Rice is most sensitive to heat stress at the flowering stage, with different degrees of heat damage in spikelets and leaves. To investigate the heat damage in spikelets and flag leaves, two rice genotypes, N22 (heat‐tolerant) and GT937 (heat‐sensitive), were subjected to a heat‐stress treatment (40 °C for 15 days). The results showed that more damaging was found in spikelets than in flag leaves and the heat stress significantly decreased the seed‐setting rate by 12.41 % in N22 and by 65.02 % in GT937. However, the difference in the net photosynthetic rate of the flag leaf between heat‐stressed and control was not significant. Moreover, the difference of temperatures in spikelets and flag leaves was attributed to the differences in heat dissipating. Under heat stress, the transpiration rate was significantly higher in flag leaves than in spikelets, and the temperature in flag leaves were at least 4 °C cooler than in spikelets. Although the spikelet temperatures did not differ significantly between the two genotypes under heat stress, spikelets of GT937 were more severely damaged than those of N22, which might result from the differences in the antioxidant capacities between genotypes. Results showed that little difference of superoxide dismutase, peroxidase and catalase activities of spikelets was found in N22, while significant reduction was found in GT937 under heat stress, compared with control. These results suggest that organ temperature is controlled mainly by transpirational cooling, and that heat stress is an indirect result of oxidative stress, rather than a direct result of heat damage.